Prevalencia de caries en niños de preescolar del colegio Simón Bolívar sede Hernando Acevedo Ortega (2023)
Early childhood caries (ECC) is a particularly destructive form of dental structures that mainly affects children under five years of age, it is considered a public health problem. Objective: To identify the prevalence of caries in preschool children of the Simón Bolívar school, Hernando Acevedo Ortega campus.